Professional Identity in Nursing: Constructions of the Student and Novice Nurse - Payne, Alayna (Université d'Ottawa / University of Ottawa, 2025)
Nurse scholars have consistently reported that identity represents a cornerstone to understanding nursing recruitment, retention, and leadership capacity. However, research has fallen short in critically examining the concept of identity and its relationship with key workforce indicators. New graduate nurses represent a particularly vulnerable group, as entry-to-practice education and the transition to practice exert a profound impact on the ways in which new graduate nurses identify with the profession, internalize core values, and enact their identity in practice landscapes thereafter. As the profession faces critical challenges related to recruitment and retention of nurses, it is imperative to understand the ways in which new graduate nurses construct a professional identity and how this impacts the work that they do. The research questions that guided this work included: how does nursing's professional identity evolve during the first six months of the transition to nursing practice? And, what are the internal and external discourses that influence its construction in relation to job satisfaction and intent to remain in the profession? Using poststructural feminism, a qualitative case study was done with 2023 graduates from a Bachelor of Science in Nursing program in British Columbia. An online survey of demographic data and the Professional Identity Scale for Nursing Students was administered to new graduate nurses in British Columbia (n=24). Six participants participated in three follow-up interviews throughout the first six months of their transition to practice. Documents mentioned by participants during interviews were also collected. Survey results were analyzed using descriptive statistics. Interview transcripts were analyzed using critical discourse analysis, followed by an analysis of two professional documents, the British Columbia College of Nurses and Midwives Professional Practice Standards and the Canadian Nurses Association Code of Ethics. Professional identity scores ranged from 26 to 79 (M = 65). Four primary discursive units of professional identity construction emerged: Institutional Constitution, Conditioned Tolerance, Constitution of Self, and Agency. Document analysis supported interview narratives highlighting core challenges associated with professional identity in nursing and the duty to provide care. Results gave rise to key implications for nursing education, practice, policy, and research. These included: developing politically foregrounded curricula, re-examining employment models for nurses as a means of increasing professional authority, establishing nurse-led clinical governance models, and conducting longitudinal research that examines professional identity development from a critical perspective.
Keywords: Bachelor of Science in Nursing; Nursing Education; Professional Identity; Novice Nurse; New Graduate Nurse; Poststructural Feminism; Critical Discourse Analysis; Qualitative Case Study